(untitled) (Bangladesh Journal of Urology, 2020)
Aim: The aim of this study is to compare the outcomes of miniaturized percutaneous nephrolithotomy (mini-perc) and retrograde intrarenal surgery (RIRS) in management of renal stones with a diameter <15 mm. Materials and Methods: This was an open-label prospective study that included a total of 80 cases underwent mini-perc (n = 40) and RIRS (n = 40) between July 2014 and August 2017. The primary outcome objective was stone-free rate, retreatment rate, complications, hospital stay, operative time, and reduction in hemoglobin level. Data were analyzed using SPSS version 16.0 Software. Results: Overall, 80 patients were enrolled in this study. The mean age was 40.12 and 38.20 years, and the mean stone size was 1.15 and 1.30 cm in mini-perc and RIRS group, respectively. Majority of the study participants were males. Overall, mini-perc and RIRS had stone clearance rates of 100% and 95.4%, respectively. Two patients required retreatment in RIRS group. The duration of hospital stay and the rate of complication was similar in both the groups. Operative duration was more in RIRS group. Decrease in hemoglobin level was more in mini-perc group. Conclusions: Results demonstrated that both modalities were associated with high stone clearance rates with minimal complications. RIRS was associated with less reduction in hemoglobin and could be used as standard treatment modality for small renal calculi. Bangladesh Journal of Urology, Vol. 23, No. 2, July 2020 p.199-204